A Cross-Sectional Study of Breast Cancer Surgery and the Cost Based on Data From 77 Chinese 3A Hospitals in 2015 - Zhao, Rong; Jin, Meng; Gao, Jinnan; Zhang, Linhui; Tao, Liyuan; Bao, Xiaoyuan (Frontiers in Oncology, 2022)
Purposes We aimed to clarify the real-world status of breast cancer surgery and the cost in China. Methods This cross-sectional survey relied on data obtained from the hospitalization summary reports (HSRs) in 77 top-ranked (grade 3A) hospitals in China to analyze breast cancer patients who underwent surgery between January 2015 and December 2015. The surgery and cost were mainly evaluated. Results Overall, 31,900 breast cancer patients underwent surgeries in 77 hospitals. The mean age in our study was 51.5 years (SD, 11.7 years). The primary types of surgical procedures were mastectomy (n = 24,629, 77.2%) and breast-conserving surgery (6,210, 19.5%). The rate of mastectomy was the highest at age band 50–65 years (n = 10,861, 82.1%) and in non-first-tier cities (n = 7,651, 88.4%) as well as in Northeast China (n = 3,107, 93.2%). The rate of breast-conserving surgery was less than 10% in non-first-tier cities (9.8%), Southwest China (6.1%), and Northeast China (5.8%). The median cost was 3,352.4 (interquartile range (IQR), 2,492.6–4,588.0). Mastectomy cost was significantly higher than breast-conserving surgery cost in both different city tiers and regional distribution except Northeast China (p < 0.001). Conclusions This study demonstrated that the main breast cancer surgery in Chinese 3A hospitals was mastectomy and that the cost varied both across and within geographic regions and city tiers. This information helps describe the real-world status of breast surgery and the cost in China.